2008
DOI: 10.1007/s00259-008-0789-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the thyroid remnant in the elevation of the serum thyroglobulin after thyroidectomy in differentiated thyroid carcinoma. Importance of the diagnostic iodine total-body scanning

Abstract: We propose to perform periodic diagnostic TBS to improve Tg specificity, at least while neck thyroid activity is detected, even if Tg is negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…The least differentiated metastases have been reported to be associated with lower Tg levels, because of a decrease in the synthesis or release of a normal Tg and the synthesis of immunologically inert Tg unrecognized by antibodies used in the routine assay, or the more rapid clearance of Tg from the plasma 14 . Of our 572 patients, 13 showed positive scans with undetectable Tg and negative TgAb, a rate similar to that previously reported 14–16 . None of our patients showed later Tg elevation, and there was no evidence of recurrent/persistent disease in any of the patients without abnormal US findings during a follow‐up of 47–100 months.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The least differentiated metastases have been reported to be associated with lower Tg levels, because of a decrease in the synthesis or release of a normal Tg and the synthesis of immunologically inert Tg unrecognized by antibodies used in the routine assay, or the more rapid clearance of Tg from the plasma 14 . Of our 572 patients, 13 showed positive scans with undetectable Tg and negative TgAb, a rate similar to that previously reported 14–16 . None of our patients showed later Tg elevation, and there was no evidence of recurrent/persistent disease in any of the patients without abnormal US findings during a follow‐up of 47–100 months.…”
Section: Discussionsupporting
confidence: 78%
“…None of our patients showed later Tg elevation, and there was no evidence of recurrent/persistent disease in any of the patients without abnormal US findings during a follow‐up of 47–100 months. Another study reported that 13 of 128 patients showed evident neck activity with undetectable Tg and negative TgAb, with none showing evidence of later Tg elevation 15 . These results suggested that such patients were not considered to have false‐negative Tg reading.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports ignored the clinical significance of radioiodine uptake in the thyroid bed after remnant ablation because of low thyroglobulin levels, which is considered a good prognostic marker [2,11-13]. However, a few recently published reports emphasized the importance of WBS [6-8]. One report concerning positive post-therapeutic WBS uptake outside the thyroid bed and negative thyroglobulin levels suggested metastatic lesions rather than false-positive image findings [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another report demonstrated that many patients were positive for thyroid bed uptake on DxWBS and negative for Tg levels after high-dose RAI. These patients responded well to additional high-dose RAI therapy, discouraging the use of a negative Tg value as an adequate solitary marker for the presence and treatment of small cervical remnants [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation